A study of the thermodynamic properties of poly[2-(3-mesityl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate] at infinite dilution using inverse gas chromatography - Kaya, I; Demirelli, K (Scientific Technical Research Council Turkey, 1999)
Some thermodynamic quantities were obtained for the interactions of poly [2-(3-mesityl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate] with alcohols, ketones, acetates, aromatics and alkanes by inverse gas chromatography in the temperature range 160-200 degrees C. The specific retention volumes, V-g(o), weight fraction activity coefficients of solute probes at infinite dilution, Omega(1)(infinity), Flory-Huggins thermodynamic interaction parameters, chi(12)(infinity) between polymer and solvents were determined. The partial molar free energy, Delta (G) over bar(1)(infinity), the partial molar heat of mixing, Delta (H) over bar(1)(infinity) at infinite dilution and the solubility parameters of the polymer, delta(2) were calculated.
Keywords: poly[2-(3-mesityl-3-methylcyclobutyl)-2-hydroxyethyl methacrylate]; inverse gas chromatography; polymer-solvent interactions